Solid state communications. (New York : Pergamon Press.)
Contains abstracts of important papers published in: Soviet physics- Solid state.
Publisher: Elsevier, <Apr. 2004-
Chemical abstracts
Also available online.
English, French, German, or Russian.
Frequency change per FAXON notice 6-24-93 (with 9046886)
Keywords: Solid state chemistry; Solid-state physics